Some analyses of pigments from Erebuni - Keheyan, Yeghis; Badalyan, Miqayel; Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The hill of Arin-berd is located in the south-eastern periphery of Yerevan, the capital of Armenia, on the northern edge of the Ararat Valley (Figure 1). On the hilltop are the ruins of a fortress built by the Urartian king Argišti I (785/780-756 BC). The fortress has been identified with certainty as corresponding to ancient Er(e)buni, which is mentioned in a number Urartian inscriptions discovered both on the site, and in Karmir-blur, as well in the Ḫorḫor annals of Argišti I in Van fortress and duplicate found in St.Sahak’s church in Van. The first information on the site goes back to 1879, when on a foothill, the first inscription of Argišti I was discovered. In 1894, an archaeological survey was conducted by A.A. Ivanovskij on behalf of the Imperial Archaeological Society of Moscow.